Repensando o consumismo: uma reflexão sobre a necessidade de um “consumo responsável” - Hillig, Clayton; Brum, Andréia Barreto do Nascimento (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
The work was developed through a literature reflecting on the need to counter consumerism,encouraged the questioning of the motives that lead us to purchase any product and adoptingactions that strengthen the education of people about the importance of preserving naturalenvironment of our planet, so damaged by the actions of man in pursuit of survival anddevelopment. Was also conducted field research on what a group of young people deemedresponsible consumption, as well as reports of practical experiences in reducing energyconsumption by implementing the practice of "r’s" green. Undoubtedly, the use of responsibledrinking is a great way to contribute to this process of recovery of natural resources of our planetand for this we need to use in everyday life, the Erres at least the four most commonly used:reduce, reuse, recycle and rethink. Rethinking where, although it was integrated with other, later,is of fundamental importance because it suggests the reflection, the most efficient way tointernalize knowledge as a higher value, necessary to our existence as individuals.